Delegation and accountability in parliamentary democracies - Strom, Kaare; Müller, Wolfgang C.; Bergman, Torbjörn (Comparative Politics, 2003)
Parliamentary democracy is the most common way of organizing delegation and accountability in contemporary democracies. Yet knowledge of this type of regime has been incomplete and often unsystematic. Delegation and Accountability in Parliamentary Democracies offers new conceptual clarity on the topic. Taking principal-agent theory as its framework, the work illustrates how a variety of apparently unrelated representation issues can now be understood. This procedure allows scholarship to move well beyond what have previously been cloudy and confusing debates aimed at defining the virtues and perils of parliamentarism. This new empirical investigation includes all 17 West European parliamentary democracies. These countries are compared in a series of cross-national tables and figures, and 17 country chapters provide a wealth of information on four discrete stages in the delegation process: delegation from voters to parliamentary representatives, delegation from parliament to the prime minister and cabinet, delegation within the cabinet, and delegation from cabinet ministers to civil servants. Each chapter illustrates how political parties serve as bonding instruments, which align incentives and permit citizen control of the policy process. This is complemented by a consideration of external constraints, such as courts, central banks, corporatism, and the European Union, which can impinge on national-level democratic delegation. The concluding chapters go on to consider how well the problems of delegation and accountability are solved in these countries. Delegation and Accountability in Parliamentary Democracies provides an unprecedented guide to contemporary European parliamentary democracies. As democratic governance is transformed at the dawn of the twenty-first century, it illustrates the important challenges faced by the parliamentary democracies of Western Europe.